New approaches to neuroimaging of central nervous system inflammation - Stoll, Guido; Bendszus, Martin (Current opinion in neurology, 2010)
Purpose of review - Inflammation is an important component not only in autoimmune but also in ischemic/degenerative disorders of the central nervous system (CNS). We here review magnetic resonance imaging (MRI)-based techniques to visualize neuroinflammation in vivo. - Recent findings - Iron oxide particles such as superparamagnetic iron oxide (SPIO) and ultrasmall SPIO (USPIO) are phagocytosed by hematogeneous macrophages upon systemic application into the circulation and allow in-vivo tracking of infiltration to the CNS due to their paramagnetic effect by MRI in experimental CNS disorders, and also in multiple sclerosis and stroke. Thereby, the size and application scheme of the iron particles is critical for interpretation of the MRI data which in addition to neuroinflammation involves passive diffusion and intravascular trapping. Targeting of inflammatory, activation-dependent enzymes such as myeloperoxidase or immune function molecules by MR contrast agents represents a molecular approach to visualize critical steps of lesion development caused by neuroinflammation. Clinical studies with Gd-DTPA in conjunction with experimental investigations employing more sensitive MR contrast agents such as gadofluorine revealed that breakdown of the blood-brain barrier and SPIO/USPIO-related macrophage infiltration occur mostly independently. - Summary - Cellular and targeted molecular MRI provides important insights into the dynamics of neuroinflammation.